Menstrual health practices in women with severe psychiatric disorders - Quadri, Syeda Kulsoom; Rahman, Mohammed Abdur; Amjad, Mariyah; S., Zohra Fatima; Razvi, Syed Shah Ali Hussain; Amrullah, Mohd; Siddiqua, Syeda Ayesha (International Journal of Research in Medical Sciences, 2025)
Background: Menstrual hygiene constitutes an essential facet of women's health and dignity. Women diagnosed with severe mental illness frequently encounter obstacles in the maintenance of personal hygiene attributable to cognitive impairments, deficits in self-awareness and reliance on caregivers. Notwithstanding its critical importance, menstrual hygiene continues to be an overlooked dimension of mental health care for this demographic. To assess and compare menstrual hygiene practices among females with severe mental illness and healthy age-matched caregivers using the Menstrual Practice Needs Scale (MPNS-36). Methods: This cross-sectional, comparative study was conducted at the Department of Psychiatry at Shadan Institute of Medical Sciences, Telangana. A total of 80 participants were recruited through consecutive sampling 40 clinically stable female patients diagnosed with schizophrenia, bipolar affective disorder or obsessive-compulsive disorder and 40 healthy female caregivers as controls. Sociodemographic and clinical details were collected using structured proformas. Menstrual hygiene practices were assessed using the MPNS-36. Data were analyzed using SPSS (22.0) and a p value of <0.05* was considered statistically significant. Results: The mean age of patients and caregivers was 34.59±5.09 years and 31.14±6.33 years, respectively. Statistically significant differences were observed in domains related to comfort with menstrual materials, adequacy of supplies and worry about running out of materials. Other domains showed no significant intergroup differences. Conclusions: Women diagnosed with severe mental illnesses exhibited both equivalent and inadequate menstrual hygiene practices in comparison to healthy control subjects. The incorporation of menstrual hygiene education within psychiatric rehabilitation programs is imperative for fostering comprehensive care.